Characterization of Spanlastic System Loaded Green Tea Extract as Antioxidant for Skin - Evelyne Santuso; Widji Soeratri; Tutiek Purwanti (Universitas Airlangga, 2023)
Background: Green tea possesses abundant polyphenols that exert antioxidant activity. However, green tea's hydrophilicity and instability limit its penetration into the skin layers. Recently, a non-ionic surfactant-based elastic nanovesicular system called spanlastic can enhance the delivery of hydrophilic and unstable substances. Spanlastic composed of vesicle builder and edge activator, which influence the characteristics of the vesicle. Objective: The study aimed to evaluate the influence of the ratio of the components on the characterization of green tea extract-loaded spanlastic using three different weight ratio of vesicle builder and edge activator that is 7:3, 8:2, and 9:1. Methods: Spanlastic is prepared by ethanol injection methods using Span 60 as vesicle builder (VB) and Tween® 60 as edge activator (EA). The characterization includes visually observed organoleptic, particle size (PS) and polydispersity index (PDI) using dynamic light scattering, entrapment efficiency (EE) and drug loading (DL) using total phenolic content assay. The most optimum ratio will be tested its zeta potential value using Zetasizer and viscosity using Brookfield Cone and Plate. Results: Selected spanlastic formula composed of Span 60 and Tween® 60 at a weight ratio of 8:2 has given characteristics as follows: entrapment efficiency 60.85±1.70%; drug loading 11.07±0.65%; the particle size is 419.70±7.42 nm; and PDI value 0.26±0.05. The prepared spanlastic has a greenish liquid form, with a zeta potential value of 28.53±2.78 mV and viscosity of 14.65±0.32 cP. Conclusion: The optimum weight ratio of vesicle builder and edge activator for green tea extract spanlastic is Span 60:Tween® 60 8:2.